Petrological characterisation of the “Tertiary quartzites” from the site of Troisdorf-Ravensberg (North Rhine-Westphalia, Germany): first insights in Middle Palaeolithic outcrop exploitation Petrologische Charakterisierung der „tertiären Quarzite“von Troisdorf-Ravensberg (Nordrhein-Westfalen, Deutschland): Erste Einblicke in die Nutzung des mittelpaläolithischen Aufschlusses - Prieto, Alejandro; Yusta, Iñaki; Pastoors, Andreas; Claßen, Erich (Hugo Obermaier-Society for Quaternary Research and Archaeology of the Stone Age, 2019)
The new excavations carried out at the site of Troisdorf-Ravensberg in 2015 have brought to light an essential part of Neanderthal daily life: the procurement mechanism of lithic raw material. The first hypothesis to understand this site propounds that it was used as a quartzite workshop or a quarry site where extractive and first knapping activities were performed in the Middle Palaeolithic. Against this background this study focusses on the petrological characterisation of the quartzites from Troisdorf-Ravensberg using a solid geoarchaeological protocol based on petrographic-stereomicroscopic petrology and geochemical composition. These procedures allowed us to characterise the “Tertiary quartzites” at this site and to establish two types and two varieties of this raw material based on the features which led us to understand the stone formative processes. The latter is related with sedimentary processes and the formation of silcretes. Preliminary data puts forward a selective extraction and exploitation of a specific facies, the secondary exploitation of a by-product type, and the discard of the last variety. This complex raw material exploitation is suggested by the technological markers observed, which connect the physical properties of the stone, based on silica cementation of the former quartz arenite, and the procurement strategies carried out by the Middle Palaeolithic people. The qualitative differences in the raw material are an important aspect of the anthropogenic selection that can be identified in the Troisdorf assemblage. Other selection criteria, especially the morphology of the raw pieces or technological requirements, certainly play also a major role, but are not part of this contribution.
CRIS-Team Scopus Importer:2024-12-16
Keywords: geoarchaeology; Middle Palaeolithic; petrography; raw material; silcrete; Wavelength Dispersive-X Ray Fluorescence